TEMBHANG MACAPAT MADURA: PERSPEKTIF SOSIOLOGI PENGETAHUAN - Edi Susanto (NUANSA: Jurnal Penelitian Ilmu Sosial dan Keagamaan Islam, 2016)
This article is about to describe Tembhang Macapat in the tradition of Madurese people, particularly in the village of Larangan Luar that is located in Larangan district of Pamekasan regency. It has been stated that Tembhang Macapat appears as cultural treasure that its existence needs to conserve. However it is as well claimed as out of dated culture since its noble and gallant values have been decreased. Hence structured and thoughtful attempts must be designed to promote Tembhang Macapat and the other traditional treasures in form of local content curriculum. Furthermore the department in charge, The Youth, Sport, and Cultural Affairs (Disporabud), must get optimally involved to look after and develop the local tradition by supporting any events of tradition development. As a result it could raise and fertilize the local tradition everlastingly or at least it is able to survive in the future time.